Initial growth and photosynthetic characteristics of Hymenaea courbaril plants submitted to different concentrations of potassium - Melo, Nayara Cristina de; Mendonça, Ane Marcela das Chagas; Rodas, Cléber Lázaro; Ribeiro, Suelen Francisca; Monteiro, Vanessa da Fontoura Custódio; Barbosa, João Paulo Rodrigues Alves Delfino (Scientia Plena, 2017)
The degradation of Cerrado biome has been increasing the demand for high quality tree seedlings, so that it is necessary to understand the nutritional requirements of these plants. Hymenaea courbaril L., known as jatobá, has a wide distribution that makes it an alternative of reforestation of degraded areas. The aim of the experiment was to evaluate H. courbaril initial growth and gas exchange characteristics under different potassium concentrations (K+). The experiment was arranged in a completely randomized design with five treatments (T0- 0, T1- 3, T2- 6, T3-9 e T4- 12 mM of K+) and four repetitions. Growth measurements were carried out every 15 days. SPAD index and gas exchange measurements were evaluated at 0, 30, and 60 days after treatment imposition. At the end of the experimental period, dry matter was evaluated, and root: shoot ratio (R:S) and Dickson quality index (DQI) were calculated The data were subjected to a one-way ANOVA and by Tukey’s test (P<0.05). The growth characteristics did not show significant difference with different concentrations of K+. At 0 and 30 days the photosynthetic traits were not different. However, at 60 days the absent- (T0), lower- (T1), and hyper- (T4) K+ concentration showed a reduction in SPAD index and gas exchanges parameters, confirming the role of this nutrient in the photosynthetic activity. Thus, regardless the K+ doses during 60 days, H. courbaril reached the growth requirements of field plantations. However, after this period the plant survival could be decreased in low K+ availability conditions.